Belt and road initiative Chinese version of "Marshall Plan"? - Feng, Da Hsuan 1945-; Liang, Hai Ming (Series on China's belt and road initiative, 2019)
This book views the Belt and Road Initiative (BRI), a bold and all-encompassing 21st century global effort by China, with unprecedented perspectives. The BRI could be summarised as a 'revitalization' of China's ancient land-based and maritime silk roads, but it should be noted that its impact on China and the world stands on the foundation of omnipresent economics and how China transforms its mindset in the 21st century.Though initiated by China, the BRI's implementation has been a many-to-many effort from the start. This multi-regional and multi-national effort is distinctly different from the one-to-many effort of the Marshall Plan. The two meaning-defining chapters of this book, 'Omnipresent Economics: The Belt and Road Initiative Underpinning' and 'Supercontinent, Neo-Renaissance and Cultural Communications: The Millennium Mindset Transformations Induced by the Belt and Road Initiative', have made it abundantly clear that the BRI discussions presented are unique.The discussions of this book could shed new light on the BRI, a long-term and profound initiative by China, which in today's global discussions and debates, are entirely confined to geopolitical and economics arenas. This book views the Belt and Road Initiative (BRI), a bold and all-encompassing 21st century global effort by China, with unprecedented perspectives. The BRI could be summarised as a 'revitalization' of China's ancient land-based and maritime silk roads, but it should be noted that its impact on China and the world stands on the foundation of omnipresent economics and how China transforms its mindset in the 21st century.Though initiated by China, the BRI's implementation has been a many-to-many effort from the start. This multi-regional and multi-national effort is distinctly different from the one-to-many effort of the Marshall Plan. The two meaning-defining chapters of this book, 'Omnipresent Economics: The Belt and Road Initiative Underpinning' and 'Supercontinent, Neo-Renaissance and Cultural Communications: The Millennium Mindset Transformations Induced by the Belt and Road Initiative', have made it abundantly clear that the BRI discussions presented are unique.The discussions of this book could shed new light on the BRI, a long-term and profound initiative by China, which in today's global discussions and debates, are entirely confined to geopolitical and economics arenas"--back cover